Tail behavior for the sum of two correlated classes of discounted aggregate claims in a time-dependent risk model. Issue 5 (4th March 2017) - Fu, Ke-Ang; Li, Jie
ABSTRACT: Consider a continuous-time risk model with two correlated classes of insurance business and a constant force of interest. Suppose that the correlation comes from a common shock, and that the claim sizes and inter-arrival times correspondingly form a sequence of random pairs, with each pair obeying a dependence structure. By assuming that the claim sizes are heavy tailed, a uniform tail asymptotic formula for the sum of the two correlated classes of discounted aggregate claims is obtained.